ANALYSIS OF KEY ASPECTS OF SOCIAL MEDIA MARKETING - Aenih, Alham Nur; Purwani, Avik Putri; Aisya, Naflah Rihhadatul; Satria, Noval (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research examines the strategies, tactics, and insights that contribute to the success of social media campaigns, with the objective of finding the transformative potential of social media as a driving force behind entrepreneurial success within the retail sector. Qualitative research methodology is used in this research, consisting of qualitative sampling, data collection, and data analysis. Several key findings regarding their social media marketing practices were yielded by the thematic analysis of the semi-structured interviews with 15 retail entrepreneurs. They are: diverse marketing strategies, importance of authenticity and storytelling. challenges and obstacles, and metrics and measurement. The results of this research amplified the dynamic and multifaceted nature of social media marketing in the retail sector. Retail entrepreneurs face a complex challenge that leads them to use several strategies to promote their brands and engage with consumers, i.e., strategic adaptation, authenticity and engagement, resource allocation, and measurement and optimization